Repair of ovine peripheral nerve injuries with xenogeneic human acellular sciatic nerves prerecellularized with allogeneic Schwann-like cells—an innovative and promising approach - Pedroza Montoya, Florencia Estefana; Tamez Mata, Yadira Alejandra; Simental Mendía, Mario Alberto; Soto Domínguez, Adolfo; García Pérez, Mauricio M.; Said Fernández, Salvador; Montes de Oca Luna, Roberto; González Flores, José R.; Martínez Rodríguez, Herminia Guadalupe; Vílchez Cavazos, José Félix (Elsevier, 2022)
Introduction: The iatrogenic effects of repairing peripheral nerve injuries (PNIs) with autografts (AGTs) encouraged the present study to involve a new approach consisting of grafting xenogeneic prerecellularized allogeneic cells instead of AGTs. Methods: We compared sheep's AGT regenerative and functional capacity with decellularized human nerves prerecellularized with allogeneic Schwann-like cell xenografts (onwards called xenografts). Mesenchymal stem cells were isolated from ovine adipose tissue and induced in vitro to differentiate into Schwann-like cells (SLCs). Xenografts were grafted in ovine sciatic nerves. Left sciatic nerves (20 mm) were excised from 10 sheep. Then, five sheep were grafted with 20 mm xenografts, and five were reimplanted with their nerve segment rotated 180° (AGT). Results: All sheep treated with xenografts or AGT progressively recovered the strength, movement, and coordination of their intervened limb, which was still partial when the study was finished at sixth month postsurgery. At this time, numerous intrafascicular axons were observed in the distal and proximal graft extremes of both xenografts or AGTs, and submaximal nerve electrical conduction was observed. The xenografts and AGT-affected muscles appeared partially stunted. Conclusions: Xenografts and AGT were equally efficacious in starting PNI repair and justified further studies using longer observation times. The hallmarks from this study are that human xenogeneic acellular scaffolds were recellularized with allogenic SCL and were not rejected by the nonhuman receptors but were also as functional as AGT within a relatively short time postsurgery. Thus, this innovative approach promises to be more practical and accessible than AGT or allogenic allografts and safer than AGT for PNI repair.